An Analysis of the Eckstein-Wilson Wage Determination Model - Ripley, Frank C. (Quarterly Journal of Economics, 1966)
Introduction, 121. — The general problem, 122. — The choice of variables, 123. — A graphical analysis, 124. — Tests for differences in means, 125. — Discriminant analysis, 126. — Principal components analysis, 130. — Conclusion, 134. — Appendix, 135.